MEWUJUDKAN LITERASI DIGITAL PADA GENERASI Z : TANTANGAN DAN PELUANG MENUJU PENDIDIKAN BERKUALITAS SDGS 2030 - Juniarty, Seni; Asariunnazwa, Ade Zihan; Rachman, Ichsan Fauzi (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The rapid digital development has brought great changes in various aspects of life, including education and learning. Digital developments in education provide many challenges and opportunities, such as in digital literacy. As Generation Z grows in the digital era in improving digital literacy, they are able to develop an attitude of online responsibility, digital ethics and critical thinking skills. In the context of Education for Sustainable Development (SDGs) 2030, it is important to understand the challenges and opportunities of digital literacy education that affect Generation Z's ability to understand and use information that comes from various sources in digital form. Digital literacy in the context of education plays a role as developing a person's knowledge and encouraging curiosity and developing creativity to process and understand good information to learn and understand. The purpose of this discussion is to find out the challenges and opportunities for education in the 2030 Sustainable Development Goals (SDGs). The type of research method used is literature review through a qualitative approach. Challenges and opportunities in digital literacy can have a positive impact and a negative impact on Generation Z. It can be concluded that, the results of this study are to find out the challenges and opportunities of digital literacy in realizing generation Z towards quality education Sustainable Development Goals (SDGs 2030).